Reflection in the writing classroom - Yancey, Kathleen Blake, author; Utah State University Press, publisher (Colorado State University. Libraries, 1998)
Kathleen Yancey's new book explores reflection as a promising body of practice and inquiry in the writing classroom. In a personable and eclectic style, Yancey develops a line of research based on concepts of philosopher Donald Schon and others involving the role of deliberative reflection in classroom contexts. Developing the ideas of reflection-in-action, constructive reflection, and reflection-in-presentation, she offers a structure for discussing how reflection operates as students compose individual pieces of writing, as they progress through successive writings, and as they deliberately review a compiled body of their work - a portfolio, for example. Reflection in the Writing Classroom will be a valuable addition to the personal library of faculty currently teaching in or administering a writing program; it is also a natural for graduate students who teach writing courses, for the TA training program, or for the English Education program.
On reflection -- Reflection-in-action -- Constructive reflection -- Reflection-in-presentation -- Reflective reading, reflective responding -- Reflection and the writing course -- Reflection and assessment -- Literacy and the curriculum -- Reflective texts, reflective writers.
Keywords: English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching; Reflection (Philosophy)